CLIMATE CHANGE AND TRADE - Aslı YILMAZ (Fırat University, 2019)
The importance of the countries’ border is eliminated in our globalized world day after day, and thus, shared spots increases. While borders drawn by man have no significance, the importance of weather and climate without borders on human life increased tremendously. States were eager to control climate before, and now they are not seen enthusiastic at all and have begun to give responsibility for each other. Thus, confidence of thinking the superiority established on climate left its place to helplessness and hopelessness as a result of increasing climate change. This responsibility should be imposed on actors rather than wait for them to take responsibility about establishing a global climate change regime, namely establishing rules to ensure minimization of the effects of exacerbated climate change. “Imposing” word could perhaps too strong because there are a lot of factors to being considered when creating international regimes. For example, governments and citizens should not feel limit in their independence. However regime to be established should not threaten economic interests, but it should provide new benefits. At the same time, states must not remain behind the other because of the regime in economic, political or any other competition area. So, if a state thinks that said regime will bring another state more advantages situation than itself, it begins to question the regime and regime can lost its legitimacy for it. State’s adoption of this regime is the most important among them all. In another words, state should be ready for this international regime in terms of domestic policy. Rules that are ready to been accepted externally must first been adopted internally and also citizens should be able to impose. It should provide the infrastructure needed to comply with these rules by its institutions and laws. Among other things, future scenarios should be well analyzed and the adaptation and mitigation strategies should be included at the same time. Factors that lead to climate change must be investigated. To reduce the impact in the short term and destroy in the long term should be the primary objective. All of these reasons, leaving the solution of this problem which has a great importance for humanity and the planet to the states may not be that wisely.